Pengaruh Latihan Aerobik dan Massage Bagi Kesehatan Lansia - Dwi Kurniawati; Herdianty Kusuma Handari (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Older adults are vulnerable to hypertension due to age-related declines in physical function. Aerobic exercise and massage are commonly used non-pharmacological interventions to improve cardiovascular health. Objectives: This study aimed to examine the effects of aerobic  exercise and back massage on blood pressure reduction in older adults. Methods: A quasi-experimental two-group pretest–posttest design was conducted involving 30 older adults assigned to an aerobic exercise group (n = 15) and a massage group (n = 15). Blood pressure was measured before and after the intervention and analyzed using a paired sample t-test. Results: Both groups showed significant reductions in blood pressure (p ≤ 0.05). The aerobic exercise group demonstrated greater decreases in systolic (12 mmHg) and diastolic (8 mmHg) pressure compared to the massage group (7 mmHg and 5 mmHg). Conclusion: Both interventions effectively reduced blood pressure, with aerobic exercise showing greater effectiveness. Keywords: Elderly, Aerobic Exercise, Massage, Blood Pressure.